A modified shadow segmentation technique for satellite images - Nandini, D. Usha; Leni, Dr. Ezil Sam (International Journal of Engineering and Technology, 2018)
Satellite images provide plenty of information about the the earth and it’s environment. However, presence of shadows hinders the image analysis process. This paper introduces a new technique for shadow identification which involves color models and an optimization algorithm. The RGB color image is transformed to C1C2C3 and HSI color images since they contain more shadow information than the RGB image. Subsequently these images are fed individually to the ant colony optimization algorithm which identifies shadows based on its properties. The resulting ouputs of the color models are combined using the Boolean operator which retrieves the binary image containing shadows.